BENTUK, FUNGSI, DAN MAKNA TABUIK PARIAMAN SERTA TABOT BENGKULU - Drs. Irwan, M.Sn., SESARIO WIDESLANIDA, Dra. Jupriani, M.Sn., (Serupa The Journal of Art Education, 2017)
The purpose of this study was to identify the shape, function and meaning Tabuik Pariaman and Tabot Bengkulu. This type of research is descriptive qualitative research. Sources of data in this study is tabuik and tabot (primary data) and informants, and literature (secondary data). Data collection procedures done through observation, interviews, and documentation. The findings of the research are: 1) Form tabuik Pariaman as many as 11 and as many as 10. The shape of Bengkulu tabot 2) Function tabuik Pariaman and tabot Bengkulu. 3) The meaning tabuik Pariaman and tabot Bengkulu.Kata kunci: bentuk, fungsi, makna, tabuik Pariaman, tabot Bengkulu